2014 International Conference on Informatics, Electronics &Amp; Vision (ICIEV) 2014
DOI: 10.1109/iciev.2014.6850826
|View full text |Cite
|
Sign up to set email alerts
|

High performance ultra-thin CdTe solar cell with Lead Telluride BSF

Abstract: The polycrystalline cadmium telluride (CdTe) is a leading photovoltaic (PV) material for the possibility of high-efficiency and low-cost thin film solar cell. The absorber material CdTe has a high absorption coefficient over 5×10 5 /cm and it has a direct bandgap of 1.45 eV, which is very close to the optimum bandgap for solar cells. In this work, numerical analysis was done utilizing AMPS (Analysis of Microelectronic and Photonic Structures) simulator to investigate the possibility of ultrathin absorber layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…In fact, the increase of Voc and FF both has the largest contribution to improve the efficiency of ultra-thin CdTe solar cell in this numerical analysis. These results of cell performances with the insertion of SnTe BSF layer are agreeable to the related published works [6,7]. In this research work, the CdTe solar cell conversion efficiency showed highest value of 22.61% (Jsc = 24.27 mA/cm 2 , FF = 0.876, Voc = 1.06 V) at 0.7 m of CdTe absorber layer with SnTe BSF layer.…”
Section: B Snte Bsf Layer Insertionsupporting
confidence: 92%
See 2 more Smart Citations
“…In fact, the increase of Voc and FF both has the largest contribution to improve the efficiency of ultra-thin CdTe solar cell in this numerical analysis. These results of cell performances with the insertion of SnTe BSF layer are agreeable to the related published works [6,7]. In this research work, the CdTe solar cell conversion efficiency showed highest value of 22.61% (Jsc = 24.27 mA/cm 2 , FF = 0.876, Voc = 1.06 V) at 0.7 m of CdTe absorber layer with SnTe BSF layer.…”
Section: B Snte Bsf Layer Insertionsupporting
confidence: 92%
“…6 that without BSF and with SnTe BSF layer, the normalized efficiency of the cells is linearly decreased with the increase of operating temperature at a temperature coefficient (TC) of -0.18%/°C and -0.16%/°C respectively. This TC indicates better stability of the cells with BSF at higher operating temperature, which are in good agreement with related published works [6,7]. Fig.6: Effects of operating temperature on normalized efficiency IV.…”
Section: Effect Of Operating Temperaturesupporting
confidence: 92%
See 1 more Smart Citation
“…Lead telluride (PbTe) has been suggested as a back contact material in 1D simulation studies. 97 XPS has suggested a low VBO between PbTe and CdTe(111) surfaces. 98 It was expected that a two-dimensional electron gas can form at the PbTe/CdTe (111) interface, probably increasing recombination but no experimental solar cell results were available until the work of Swartz et al (2019).…”
Section: Group IV Telluridesmentioning
confidence: 99%
“…The main purpose of providing a BSF layer in the structure of solar cells is to reduce the barrier width in the valence band and to reduce the recombination losses at the back surface of the CdS/CdTe solar cell [ 7 , 8 , 9 ]. The main technical problems of CdS/CdTe solar cells are related to higher efficiency, less material usage, and stable back contact formation [ 10 , 11 ]. These problems should be addressed and numerically evaluated to discover the unseen potentiality of CdS/CdTe solar cells for higher cell performance [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%